60‐Hz Frequency Effect on Gait in Parkinson's Disease With Subthalamic Nucleus Deep Brain Stimulation. Issue 8 (24th October 2013) - Phibbs, Fenna T.; Arbogast, Patrick G.; Davis, Thomas L.
<x xml:space="preserve">Abstract</x> Objective Gait dysfunction is common in advancing Parkinson's disease and has a disappointing response to dopamine replacement and subthalamic nucleus deep brain stimulation programming parameters. Low‐frequency stimulation, less than 130 Hz in combination with increased voltage, has been shown to decrease freezing episodes and number of steps with little impact on overall performance measured by the Unified Parkinson's Disease Rating Scale. This was in the setting of delivering the same total energy, which required both a change in voltage and frequency. We wanted to determine if the benefit came from low frequency alone. Materials and Methods We enrolled 20 Parkinson's patients who were at least three months in postbilateral subthalamic deep brain stimulation and reported gait changes. Subjects held their Parkinson's medications overnight, and following a baseline evaluation, they were randomly assigned to both 60 and 130 Hz stimulation in a blinded fashion with all other parameters held constant. Each subject was set at each frequency twice during the study, with a 60‐min stimulation interval prior to each gait evaluation. Results There was no significant difference between the two frequencies, with the primary outcome measure of stride length. Two of the 20 patients reported a significant subjective improvement in their gait with no statistical difference in their outcomes. There also was less tremor control at 60 Hz. Conclusion We were unable to demonstrate improved gait with lower frequency stimulation as suggested by prior studies. This may have been because of the decreased energy delivered from the lower frequency and unchanged voltage.